Pengujian sistem keamanan wireless router pada ekosistem rumah cerdas berbasis NIST sp800-115 - Kusuma, Mandahadi; Hariyadi, Dedy; Kurniawan, Hendarto; Muttaqin, Filda Fikri Faizal (Universitas Muhammadiyah Riau, 2023)
It is important to safeguard personal information captured by the device being used against theft or unauthorized use, which makes network design that is more resistant from hacking attempts. This includes personal information within the ecosystem of smart homes. A house that should be the most comfortable place should not be disturbed because of the wrong configuration of the smart home ecosystem. Several previous studies have discussed security configuration gaps in network infrastructure, but have not focused on the smart home ecosystem from the user's internal side. Therefore, in this research, a 2.4 GHz wireless network configuration testing model is proposed in a smart home ecosystem using an application developed specifically for checking misconfiguration security gaps, which is expected which is expected to expand research on network infrastructure security gaps based on the NIST 800-115 framework. The application's testing technique can reveal details about a wireless network ecosystem's safe and risky conditions. The results of these findings will provide recommendations to wireless network owners to take action to reconfigure their wireless networks to make them more secure.